Outcomes of lenvatinib therapy in poorly differentiated thyroid carcinoma - João Roque; Tiago Nunes Silva; Catarina Regala; Ricardo Rodrigues; Valeriano Leite (European Thyroid Journal, 2023)
Background and objective: Lenvatinib showed promising results in a subgroup of patients with poorly differentiated thyroid carcinoma (PDTC) in the SELEC T trial. Our aim was to report the effectiveness and tolerability of lenvatinib in our s eries of PDTC patients. Methods: Medical records of eight consecutive patients with PDTC treated with lenvatinib in a single center between January 2019 and October 2022 were retrospectively reviewed. Inclusion criteria were PDTC diagnosis based on Turin criteria and evidence of disease progression in the previous 6 months. Results: Eight PDTC patients received an average dose of lenvatinib of 18.1 mg for a median duration of treatment of 10.3 months. The baseline Eas tern Cooperative Oncology Group performance status was ≥2 in 50% of patients. Two patients had unresectable primary tumor. Seven patients showed extrathyroidal disease, particularly mediastinal lymph nodes (85.7%), lung (71.4%), and bone (71.4%) . The disease control rate was 100%, with partial response and stable disease in 12.5 and 87.5%, respectively. The median time to best overall response was 3 months, and the median duration of response was 7.5 months. Median progression-free survival was 1 2 months and median overall survival was not reached. At 6, 12, and 18 months, over all survival was 87.5, 71.4, and 57.1%, respectively. All patients experienced drug-related adverse effects (AEs). Four (50%) had dose reductions and two (25%) had temporary trea tment interruptions. Lenvatinib was stopped in two patients due to grade ≥3 AEs. Conclusion: Lenvatinib is an effective treatment for real-world PDTC patien ts. Adequate management of comorbidities and AEs increases treatment tolerability and minimizes dose reductions.